Ultrahigh mobility and efficient charge injection in monolayer organic thin-film transistors on boron nitride - He, Daowei (Sci Adv, 2017)
Organic thin-film transistors (OTFTs) with high mobility and low contact resistance have been actively pursued as building blocks for low-cost organic electronics. In conventional solution-processed or vacuum-deposited OTFTs, due to interfacial defects and traps, the organic film has to reach a certain thickness for efficient charge transport. Using an ultimate monolayer of 2,7-dioctyl[1]benzothieno[3,2-b][1]benzothiophene (C(8)-BTBT) molecules as an OTFT channel, we demonstrate remarkable electrical characteristics, including intrinsic hole mobility over 30 cm(2)/Vs, Ohmic contact with 100 Ω · cm resistance, and band-like transport down to 150 K. Compared to conventional OTFTs, the main advantage of a monolayer channel is the direct, nondisruptive contact between the charge transport layer and metal leads, a feature that is vital for achieving low contact resistance and current saturation voltage. On the other hand, bilayer and thicker C(8)-BTBT OTFTs exhibit strong Schottky contact and much higher contact resistance but can be improved by inserting a doped graphene buffer layer. Our results suggest that highly crystalline molecular monolayers are promising form factors to build high-performance OTFTs and investigate device physics. They also allow us to precisely model how the molecular packing changes the transport and contact properties.